Mechanical Properties of Single-Walled Carbon Nanotubes by Molecular Mechanics Model - Bahari, A.; Eimeri, R.; Rasuli, Sh.; Farhang, H.; Fadai, M. (Asian Journal of Chemistry, 2010)
Many researchers have studied the mechanical properties of carbon nanotubes with various theoretical descriptions. There are still some discrepancies which need to further explore the mechanical properties of carbon nanotubes. The radial deformation is of significant interest in the analysis of nanotube-structural systems. Thus, the variation of mechanical properties was studied with tube diameter. In the present work, attention is paid to provide a very simple approach to formulate the radial deformation of single wall carbon nanotubes and derive in-plane stiffness in the hoop direction Y and Poisson ratio vzθ of carbon nanotubes under radial pressure. It means that both Y and vzθ are highly sensitive to tube diameter and decrease exponentially with increasing tube diameter but Y of zigzag is more sensitive to an increase in the tube diameter than armchair. The present developed analytical modeling approach predicts that Young modulus and Poisson ratio of single wall carbon nanotubes varies from 0.1 to 0.5 TPa and 0.6 to 1.9, respectively.